The development of the methodical approach to the auditing of agricultural land leasing - Бурлан, Світлана Анатоліївна; Каткова, Наталя Володимирівна; Матушевська, Олена Анатоліївна (Technology audit and production reserves, 2016)
The article proves the necessity of auditing of land leasing of agricultural enterprises: synthesize. The aim, the tasks and the objects of audit of agricultural land leasing are summarized and developed. The implementation of the recommended methodological approach to auditing allows to get all the necessary and sufficient audit evidence to form auditor's opinion on the legality of leases of land and reliability of the recording and reporting of agricultural enterprises. Based on the peculiarities of agricultural leasing the methods for auditing operations of land leasing are designed. Comparing to the existed approaches it is oriented to making the legal auding of leased land. To confirm and ensure the validity of the audit report the pack of auditor's working papers is formed, which allows to analyze and summarize the results of the auditing of land leasing transactions. The using of the proposed auditor's working documents provides the necessary level of the audit report validity and the control of all planned procedures on leasing transactions.